Sistem Pendukung Keputusan Kenaikan Jabatan Bagian Produksi Menggunakan ROC dan ARAS - Yuri Rahmanto (PT. Tech Cart Press, 2024)
Promotion in the production department is an important step that can improve the company's performance and operational efficiency. By promoting highly competent employees, leadership abilities, and a deep understanding of the production process, companies can ensure that production teams are led by individuals who are able to effectively manage resources, drive innovation, and improve output quality. One of the main problems is the existence of subjectivity in performance evaluation, where decisions can be influenced by personal preferences or inter-individual relationships, rather than on objective performance and competence. The purpose of this study is to provide tools that are easy to use by management in the process of evaluating and promoting employees, in order to support an effective and targeted decision-making process in the production environment by applying rank order centroid (ROC) and additive ratio assessment (ARAS) methods. So that it can make a real contribution in optimizing a fair and data-based promotion process in the production department, as well as increasing employee satisfaction and trust in the company's promotion policies. The result of the promotion recommendation that the candidate who received the highest rank was Candidate 5 with a score of 0.9305. These candidates are assessed as the ones who best meet the set criteria. Candidate 8 and Candidate 2 occupy the next position with values of 0.8684 and 0.8565. The results of this recommendation provide a clear picture of the performance and potential of each candidate, so that it can help the company in making fair and appropriate decisions in the process of promotion in the production department.